Comparing Short-term and Oncologic Outcomes of Minimally Invasive Versus Open Pancreaticoduodenectomy Across Low and High Volume Centers - Torphy, Robert J; Friedman, Chloe; Halpern, Alison; Chapman, Brandon C; Ahrendt, Steven S; McCarter, Martin M; Edil, Barish H; Schulick, Richard D; Gleisner, Ana (Annals of surgery, 2019)
To compare short-term and oncologic outcomes of patients with cancer who underwent open pancreaticoduodenectomy (OPD) versus minimally invasive pancreaticoduodenectomy (MIPD) using the National Cancer Database. MIPD, including laparoscopic and robotic approaches, has continued to gain acceptance despite prior reports of increased short-term mortality when compared with OPD. Patients with pancreatic cancer diagnosed from 2010 to 2015 undergoing curative intent resection were selected from the National Cancer Database. Patients submitted to OPD were compared with those submitted to MIPD. Laparoscopic and robotic approaches were included in the MIPD cohort. The primary outcome was 90-day mortality; secondary outcomes included 30-day mortality, hospital length of stay, unplanned 30-day readmission, surgical margins, number of lymph nodes harvested, and receipt of adjuvant chemotherapy. Propensity score-weighted random effects logistic regression models were used to examine the adjusted association between surgical approach and the specified outcomes. Between 2010 and 2015, 22,013 patients underwent OPD or MIPD for pancreatic cancer and 3754 (17.1%) were performed minimally invasively. On multivariable analysis, there was no difference in 90-day mortality between MIPD and OPD (OR, 0.92; 95% CI, 0.75-1.14). Patients undergoing MIPD were less likely to stay in the hospital for a prolonged time (OR, 0.75; 95% CI, 0.68-0.82). 30-day mortality, unplanned readmissions, margins, lymph nodes harvested, and receipt of adjuvant chemotherapy were equivalent between groups. Regardless of surgical approach, patients operated on at high volume centers had reduced 90-day mortality. Patients selected to receive MIPD for cancer have equivalent short-term and oncologic outcomes, when compared with patients who undergo OPD.